The Prevalence of Staphylococcus Aureus Isolated from Skin and Soft Tissue Infections and Its Antibiotic Susceptibility Patterns - Asma Omar Ali; Miftah Najm (AlQalam Journal of Medical and Applied Sciences, 2021)
Objectives: The current study was aimed to evaluate the frequency and antibiotic susceptibility pattern of S. aureus isolated from various clinical specimens of patients admitted to Al Jala hospital during 2017 and 2018, and to figure out the prevalence of S. aureus strains among clinical specimens. Methods. A cross sectional study conducted in AL jala hospital during 2017-2018. About 226 clinical specimens were collected and inoculated in sheep blood agar, chocolate, and mannitol salt agar. Then incubated at 35 c for 18-24 hours in aerobic atomosphere. The Kirby-bauer disc diffusion method was performed to determine antibiotic susceptibility. Results. Most of staph aureus isolate were from ages 21-30 years, followed by ages 31-50 years, while in 2018, the most of staph aureus isolate were from ages 31-50 year followed by 17-30 years. The highest isolate of staph aureus from clinical specimens was in males than in females in both years. The highest specimen found in the swab was staph aureus followed by tips and pus. The highest susceptibility level of Staph aureus during 2017 was recorded towards Vancomycin, followed by Ciprofloxacin (70%), Septrin (66%), Erythromycin and Amikacin 85(60) equally. While, the highest resistance level recorded was towards Amoxicillin (46%) followed by Tetracycline (32%), Gentamycin 34 (24%). In 2018, S. aureus strains recorded high sensitivity to Ciprofloxacin and Erythromycin 83 (81%) equally. The most common drug resistance was colistin 101 (99%), Augmentin 93 (91%) and ceftazidime 77 (75%). Conclusion. Vancomycin, Ciprofloxacin and Erythromycin were the most antibiotics found to give constant sensitivity. The determination of prevalence and antibiotic sensitivity pattern of staph aureus will assist clinicians to establish antibiotic treatment approaches.